Efforts to Improve Teacher Performance Through Individual Supervision of Dumai 6 Public Middle School Teachers - Andi Effendi (Journal of Educational Sciences, 2023)
The purpose of this research is to improve teacher performance through individual supervision of SMP Negeri 6 Dumai, East Barito Regency. The method used in this research is Action Research which consists of 2 (two) cycles, and each cycle consists of: Planning, Implementation, Observation, and reflection. Based on the results of action research that individual supervision can improve the performance of SMP Negeri 6 Dumai, East Barito Regency. Furthermore, the researcher recommends: (1) Principals who experience the same difficulties can use Individual Supervision as a solution. (2) In order for the implementation of Individual Supervision to get maximum results, it is hoped that the Principal will carry out Individual Supervision intensively and continuously.